Coupled Fixed Point Theorems of Single-Valued Mapping for c-Distance in Cone Metric Spaces - Zaid Mohammed Fadail; Abd Ghafur Bin Ahmad (Journal of Applied Mathematics)
A new concept of the c-distance in cone metric space has been introduced recently in 2011. The aim of this paper is to extend and generalize some coupled fixed-point theorems on c-distance in cone metric space. Some examples are given.